1996
DOI: 10.1021/ma951261+
|View full text |Cite
|
Sign up to set email alerts
|

Ordering Dynamics of Compositionally Asymmetric Styrene−Isoprene Block Copolymers

Abstract: We investigate the development of mesophase order in compositionally asymmetric (13 wt % styrene) polystyrene−polyisoprene (SI) diblock and SIS triblock copolymers. The equilibrium ordered morphology of these polymers is a body-centered-cubic (bcc) lattice of spherical S microdomains. The ordering kinetics are measured by quenching the material from above the order−disorder transition temperature (T ODT) to a temperature where the ordered phase is stable and following the structure development by time-resolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
198
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(222 citation statements)
references
References 39 publications
(108 reference statements)
22
198
2
Order By: Relevance
“…Whether the solutions are ordered [body-centered-cubic (BCC) lattice of spheres] or disordered is easily assessed rheologically, as they show the same signatures that we have described previously for the bulk materials. 16,20 For the tests described herein, all concentrated solutions remained in the metastable disordered state throughout the measurements, as evidenced by identical low-frequency moduli at the start and end of rheometric testing. These tests also confirm that no measurable degradation of polymer or evaporation of squalane occurred during the tests.…”
Section: Viscoelastic Measurementsmentioning
confidence: 86%
See 3 more Smart Citations
“…Whether the solutions are ordered [body-centered-cubic (BCC) lattice of spheres] or disordered is easily assessed rheologically, as they show the same signatures that we have described previously for the bulk materials. 16,20 For the tests described herein, all concentrated solutions remained in the metastable disordered state throughout the measurements, as evidenced by identical low-frequency moduli at the start and end of rheometric testing. These tests also confirm that no measurable degradation of polymer or evaporation of squalane occurred during the tests.…”
Section: Viscoelastic Measurementsmentioning
confidence: 86%
“…15,16 Table I summarizes the relevant molecular characteristics of these systems; the sample code identifies these polymers by their block chemistry and approximate weight-average molecular weight (M w ; kg/mol). Gel permeation chromatography (GPC) in toluene, referenced to narrow-distribution polystyrene standards, was employed recently to redetermine the true M w of the block copolymers, according to the method described by Sebastian and Register.…”
Section: Experimental Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The small angle X-ray scattering measurement of the above sample, which was analyzed assuming a twodomain structure, indicated that PS forms spheres of 16.4 nm in a body-centered-cubic lattice. 16 The interspherical distance was found to be 30.2 nm. The above data can be converted to an equivalent cube of 13.2 nm for the PS domain and 26.7 nm for the long cubic period.…”
Section: Methodsmentioning
confidence: 94%